Os verbos recíprocos no PB: Interface sintaxe-semântica lexical - Luisa Andrade Gomes Godoy (2008)
This dissertation aims to study the reciprocal verbs in Brazilian Portuguese (BP). These verbs behave syntactically in two ways: one way is the reciprocal verbs simple form, in sentences like João e Maria conversaram (in which the participants of the reciprocity relation are denoted by a single argument) and the other way is the reciprocal verbs discontinuous form, in sentences like João concorda com Maria (in which the participants of the reciprocity relation are denoted by two separate arguments). The first half of this text contains a description of the reciprocal verbs as a verbal class in BP. Using a test developed to identify reciprocal verbs, we listed over 200 verbs in BP, from which we picked the 126 most common ones for our data. We demonstrate how these verbs have different transitivity patterns and different thematic grills. Then, we ponder on the notion of verbal class, assuming the hypothesis that there are semantic properties in the items lexical information that determine their syntactic behavior. The semantic property shared by the reciprocal verbs is reciprocity, no matter what thematic grill they have. Reciprocity determines these verbs syntactic behavior: the alternation between a simple and a discontinuous form, no matter what transitivity pattern they have. Therefore, we show that reciprocity is a grammatically relevant semantic property. We also discuss the nature of this property, that seems to belong to the verbs logic meaning. The second half of this text contains a lexical-semantic analysis of the simple-discontinuous alternation. Adopting Cançados (2005a) proposal for thematic roles, we answer a current question in linguistic literature: are simple and discontinuous sentences synonymous? We demonstrate how these forms cannot be used to describe the same event, therefore, they are not synonymous. A simple form describes a symmetric reciprocal eventand a discontinuous form describes an asymmetric reciprocal event. So, we distinguish the two notions: reciprocity and symmetry. We then go onto the nature of the simple-discontinuous alternation, for it differs from merely syntactic alternations like the active-passive one. The simple-discontinuous alternation involves not only a variation in syntactic structure, but also a variation in the number of arguments in the argument structure. Pursuing the idea that a reciprocal verb does not have two argument structures (each related to a syntactic form), we propose a single argument structure for each verb. Finally, what we seek is to corroborate the hypothesis that a grammatical phenomenon, like the syntactic alternation presented by reciprocal verbs, can be explained from a semantic point of view. Because we deal with lexical-semantic aspects related to a syntactic phenomenon, its possible to say that this research has an interface perspective.